Quantum transport in functionalized epitaxial graphene without electrostatic gating. (30th April 2021) - Lock, E.H.; Prestigiacomo, J.C.; Dev, P.; Nath, A.; Myers-Ward, R.L.; Reinecke, T.L.; Gaskill, D.K.; Osofsky, M.S.
Abstract: Graphene, the first isolated two-dimensional material, has captivated researchers for the last decade due to its unique structure that leads to novel electronic, chemical, mechanical, and thermal properties. The most intriguing properties are the large electronic mobilities that are achievable for low carrier concentrations and the large tunability of graphene's electrical properties via electrostatic gating, in which the Fermi energy is shifted relative to the charge neutrality, or Dirac, point and the high electronic mobilities obtained when the Fermi energy is close to that point. In this report, we show that both covalent and non-covalent functionalization of graphene leads to adsorbate-induced doping. This results in a three-fold increase in the graphene systems' mobilities and the observation of quantum transport phenomena (Hall effect plateaus, Shubnikov-de Haas oscillations, and Berry's phase) which were not observed in the unfunctionalized graphene. This ability to control the electronic properties without electrostatic gating is critical for chemical and biological sensing, optical, and electronic applications, which require both low carrier concentrations and the attachment of nanocrystals, biomolecules, increased adhesion and wettability of graphene layers, and enable strong cohesion between graphene layers in stacked graphene structures.